2020
DOI: 10.1108/jocm-02-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

Beyond gender: reconceptualizing understandings of work–life balance and the extreme work model for 21st-century high-potential top earners

Abstract: PurposeThe purpose of this study is to broaden an understanding of women's perceptions regarding advancement potential/barriers to success in upper echelon corporate roles in the S&P 500 in connection with understanding 21st-century family dynamics, rather than addressing gender in isolation.Design/methodology/approachData collection in this study is based on semi-structured phone interviews with 13 women who have been identified by organizational leadership in an S&P 500 company as having high advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…While such perspectives are useful, it is also important to avoid the creation of a false dichotomy and to consider the broken pipeline of women's advancement in Corporate America in a holistic manner that accounts for the complexity of the situation in relation to the presence of a well-entrenched extreme commitment "24/7" (Hewlett & Luce, 2007, p. 54) work culture (DeSimone, 2020;Hewlett & Luce, 2007;Thornton, 2016). For example, the understanding of motherhood as a pull variable runs contrary to the notion that the extreme work model forces this choice thereby rendering it a push variable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…While such perspectives are useful, it is also important to avoid the creation of a false dichotomy and to consider the broken pipeline of women's advancement in Corporate America in a holistic manner that accounts for the complexity of the situation in relation to the presence of a well-entrenched extreme commitment "24/7" (Hewlett & Luce, 2007, p. 54) work culture (DeSimone, 2020;Hewlett & Luce, 2007;Thornton, 2016). For example, the understanding of motherhood as a pull variable runs contrary to the notion that the extreme work model forces this choice thereby rendering it a push variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, although women represent 57% of the overall workforce and approximately 46% of management, they are underrepresented in the upper echelons of organizations with women representing approximately 15% of Fortune 500 executive officers, 11% of corporate top earners, 21% in board seats, and only 5.2% in the role of CEO (Catalyst, 2017). In addition to this issue-which clearly constitutes a broken pipeline in terms of women's advancement to the executive level, top earner positions-many women report feeling that, given the prevalence of an extreme work culture and institutional advancement initiatives, any barriers they face are self-imposed (DeSimone, 2020;Harris, 2017;Hewlett & Luce, 2007;Thornton, 2016). Harris (2017) andSandler (2014) studies confirmed that negative self-limiting ideologies prevent women from appreciating their full professional advancement potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation